Design Lighting System Based on PID Control and Node-RED - Muhammad Fikrul Ma’arif (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
In general, lighting systems use the on/off principle, by turning on the lights in a dark room and turning off the lights in a bright room. This has drawbacks in terms of effectiveness, because it does not pay attention to external influences and lighting, namely sunlight. To overcome this problem, automatic light intensity control is needed which still refers to the surrounding lighting. The aim of this research is to understand the performance of light intensity control devices in lighting systems using the PID method. Comparing the measurements of the BH1750 sensor with a lux meter measuring instrument, an average error value of 6.61% was obtained. Searching for PID parameters uses the trial and errors method with 5 attempts on each parameter. In testing each parameter, optimal results were obtained for the PID parameters, namely Kp = 0.10 Ki = 0.18 Kd = 0.10 with a system response value of 7.91, settling time of 14.63 and overshoot of 0.97